The Role of Active Games in The Physiological Development of Middle School-Aged Children - Safarova, Zakiya Teshayevna; Turayev, Muxtor Murodovich (Universitas Muhammadiyah Surakarta, 2025)
The article examines the importance of active games for the physiological development of middle school-aged children. An analysis was conducted on the impact of regular physical activity, implemented through active games, on key indicators of children's health and physical condition. Special attention is given to the development of the cardiovascular, respiratory, and muscular systems, as well as improvements in coordination and overall endurance. The study’s results confirm that incorporating active games into the daily routine contributes to harmonious physical development, health strengthening, and increased levels of motor activity among schoolchildren. The conclusion emphasizes the necessity of integrating active games into the educational process to optimize the physiological development of children.